SEASONAL VARIATION IN THE PHYSICOCHEMICAL PARAMETERS OF DABERAM RESERVOIR DUTSI, KATSINA STATE, NIGERIA - Sadauki, M. A.; Ochokwu, Jane; Hadiza, Y. B. (FUDMA Journal of Sciences, 2022)
The knowledge of the physicochemical values of Dan buran reservoir is optimal for proper functioning and growth of the aquatic organisms, for the health of the individual that directly consume the water, and also beneficial towards the sustainability of the aquatic animals. The study ascertained the dissolve oxygen, pH, temperature, hardiness, phosphate, turbidity, alkalinity and ammonia levels of Dan buran Reservoir in Dutsi Local Government Area of Katsina State. The water samples were collected from three different sites in an air tight container from January to December 2021, and were transported to the Biological Science Department at Federal University Dutsin-Ma for evaluation. The line graph were used to present the results, while regression was further used to compare the relationship among the parameters. The results uncovered that the physicochemical parameters significantly differed from each site and season. The lowest temperature was recorded in the months of December (21.5), January (19.1), February (20.4), while the highest temperature was in the month of June (30.3). Meanwhile, turbidity was highest in the month of May and June (18.0 to 18.6) and the lowest value were obtained in the month of September and October (4.1 to 5.0). Meanwhile, in the aspect of dissolved oxygen, the month of August had the lowest value (6.2), followed by February, March, April and July which had the highest level of dissolved oxygen (7.6). There were regression relationship between temperature and other physicochemical parameters in this study
Keywords: Variation in season, Physicochemical Parameters and Dan buran Reservoir